AB1015 Mortality Rate According To Cause in Patients with Hemophagocytic Lymphohistiocytosis: A Meta-Analysis. (15th July 2016) - Sheth, K.; Kuo, C.-L.; Modi, D.; Nanavaty, S.; Scola, C.
Abstract : Background: Hemophagocytic lymphohistiocytosis (HLH) is a rare syndrome of excessive immune activation associated with high mortality. Early diagnosis and treatment can reduce mortality among these patients. Objectives: To determine the rate of mortality independently and according to the cause in patients with HLH. Methods: Pubmed database with the MeSH terms ("lymphohistiocytosis, hemophagocytic" [MeSH Terms] OR ("lymphohistiocytosis" [All Fields] AND "hemophagocytic" [All Fields]) OR "hemophagocytic lymphohistiocytosis" [All Fields] OR ("hemophagocytic" [All Fields] AND "lymphohistiocytosis" [All Fields])) AND cases [All Fields] were queried which yielded 466 results. Case series referenced from these studies were also studied. 74 studies were identified out of which the studies with a sample size smaller than 10 were excluded. 48 studies were kept with a total of 1983 patients. Meta analysis was performed to combine the mortality rates of all studies and studies of patients with the same cause. The results were presented in a Forest plot. Prior to the meta analysis, the heterogeneity test on mortalities was conducted to choose a fixed or random effects model. I 2, a common heterogeneity measure, was reported with 25%, 50%, 75% suggesting low, moderate, and high heterogeneity. Results: The combined mortality rate for all studies was 41.99% [95% confidence interval (CI) 36%>49%]. In studies of patients with EBV infection (n=4), the combined mortality rate was 44% (95% CI 18%>74%) whereas the mortality rate in studies with other infections (n=4) was 46% (95% CI 13–83%). The mortality rate in patients with hematological malignancy (n=8) was higher at 60% (95% CI 44%>74%]. For studies of patients with autoimmune diseases (n=2) and in transplant (n=4) patients, the combined mortality rate was 11% (95% CI 5%>21%) in patients with autoimmune disease and 38% (95% CI 27%>51%) in transplant patients. I 2 for the mortalities of all studies and each cause was presented as follows: I 2 =0% (p=0.764) for autoimmune disease, I 2 =94.8% [89.6%; 97.4%] (p<0.0001) for EBV infection, I 2 =75.2% [50%; 87.7%] (p=0.0002) for hematological malignancy, I 2 =75.2% [50%; 87.7%] (p=0.0002) for infection malignancy, I 2 =89.2% [75.1%; 95.3%] (p<0.0001) for other infection, and I 2 =0% [0%; 52.1%] (p=0.811) for transplant. The heterogeneity test result remained significant but for the causes of autoimmune disease and transplant. Conclusions: Based on our results, mortality is higher in patients with hematological malignancy compared to patients with other causes, whereas it is lower in patients with autoimmune disease. Disclosure of Interest: None declared